This I Believe - Reicher, Clement (Tufts Archival Research Center, 2006)
Clement Reicher recounts a short allegory he wrote as a child which formed the basis for his belief that love must be personal (not idea-driven) and unpossessive, in order to increase and lead ultimately to happiness.